Nutritional and Sensory Evaluation of Dangke-Based Nuggets as a Nutrient-Dense Supplementary Food for Stunting Prevention in Indonesia - Mertien Sapang; Harna Harna; Abdul Salam; Seprianto Seprianto; Titis Retno Sawitri (Journal of Health and Nutrition Research, 2026)
Stunting remains a major nutrition challenge among children under five years in Indonesia. The development of nutrient-dense supplementary foods utilizing traditional food resources offers a sustainable strategy for stunting prevention. Dangke, a traditional Indonesian cheese from Enrekang, South Sulawesi, is rich in protein and calcium and has potential as a functional ingredient in supplementary foods for toddlers. This study aimed to develop and evaluate dangke-based nuggets as an alternative supplementary food for toddlers. Four nugget formulations containing different proportions of dangke (0%, 18%, 35% and 52%) were developed and evaluated. Sensory acceptability (taste, color, aroma and texture) was assessed by 25 semi-trained panelists and 26 consumer panelists. Data were analyzed using One-Way ANOVA followed by Duncan’s post-hoc test. Proximate analysis, calcium content, and amino acid profiling were performed. Sensory evaluation demonstrated that all formulations were generally acceptable, with F3 receiving the highest consumer preference scores for taste (p= 0.011) and texture (p= 0.024). Nutritional analysis revealed significant increases in energy, fat, protein, calcium, and several essential amino acids as the proportion of dangke increased (p < 0.05). The F3 formulation exhibited the highest nutritional value, containing 235.04 kcal energy, 11.95 g protein, 11.92 g fat, and 329.08 mg calcium per serving. Amino acid analysis showed enhanced levels of alanine, aspartic acid, cystine, methionine, and tryptophan in formulations with higher dangke content. The product shows potential as a locally sourced supplementary food to support toddler nutrition and promote the utilization of traditional Indonesian foods. However, further studies are needed to evaluate its effectiveness in improving dietary intake and nutritional outcomes among young children.